2004
DOI: 10.1590/s0100-06832004000400008
|View full text |Cite
|
Sign up to set email alerts
|

Peanut response to lime and molybdenum application in low pH soils

Abstract: SUMMARYLiming acid soils is considered to assure the availability of Mo in crops. Additionally, in peanuts (Arachis hypogaea L.) the positive response to liming is associated to a better supply of Ca +2 , Mo for the nitrogenase-complex activity, and other non-nitrogen fixing activities of the crop. This study was thus undertaken to assess the effect of lime, Mo, and the lime-Mo interaction on peanut crop, on an acid Ultisol at the Mococa Experimental Station, Instituto Agronômico, São Paulo State, Brazil, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 7 publications
1
18
0
5
Order By: Relevance
“…In the present study, we observed a marked increase in seed yield of green gram, about 33.2% at 0.075 mg kg À1 level of Mo. A similar increase (28%) was also observed by Quaggio et al (2004) in peanut yield at the rate of 0.186 kg ha À1 Mo through soil application. Bhattacharya et al (2004) reported that adequate NPK fertilization increased green gram and black gram [Vigna mungo (L.) Hepper] yields by 13 and 38%, respectively, over the control but further inclusion of B and Mo improved yield by 38% in green gram and 50% in black gram over the control in red and lateritic soils.…”
supporting
confidence: 86%
“…In the present study, we observed a marked increase in seed yield of green gram, about 33.2% at 0.075 mg kg À1 level of Mo. A similar increase (28%) was also observed by Quaggio et al (2004) in peanut yield at the rate of 0.186 kg ha À1 Mo through soil application. Bhattacharya et al (2004) reported that adequate NPK fertilization increased green gram and black gram [Vigna mungo (L.) Hepper] yields by 13 and 38%, respectively, over the control but further inclusion of B and Mo improved yield by 38% in green gram and 50% in black gram over the control in red and lateritic soils.…”
supporting
confidence: 86%
“…Since S. hortensis L. is characterized as calcicole species and in natural habitats it is mainly found in calcareous soils (Ghahraman, 1996), this plant responded to higher levels of soil CaCO 3 content more positively than other species. Moreover, Quaggio et al (2004) mentioned that the effect of CaCO 3 treatment on peanut yield depends on many factors including the initial Ca and Mo status of the soil, time of CaCO 3 application and the peanut cultivar. The increase in plant growth and yield at 5 t ha -1 CaCO 3 could be explained by several reasons including enhancement of exchangeable Ca and Mg, increase of available Mo, decrease of Al, Mn and heavy metals toxicity due to increase of pH and improvement of soil characteristics (increase of pore volume and optimum moisture content) (Quaggio et al, 2004;Bakker et al, 2005;Rajasekaran, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Quaggio et al (2004) mentioned that the effect of CaCO 3 treatment on peanut yield depends on many factors including the initial Ca and Mo status of the soil, time of CaCO 3 application and the peanut cultivar. The increase in plant growth and yield at 5 t ha -1 CaCO 3 could be explained by several reasons including enhancement of exchangeable Ca and Mg, increase of available Mo, decrease of Al, Mn and heavy metals toxicity due to increase of pH and improvement of soil characteristics (increase of pore volume and optimum moisture content) (Quaggio et al, 2004;Bakker et al, 2005;Rajasekaran, 2005). It seems that the decrease in growth by application of 10 t ha -1 CaCO 3 could be related to excessive Ca content of soil solution, which causes precipitation of P, S and Zn (Wenming, 2001;Bakker et al, 2005;Rajasekaran, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Both negative and positive effects of liming on the availability of nutrients in acid soils and subsequent uptake by crops have been reported (Quaggio et al, 2004;Kovacevic et al, 2006). There is limited information on the transformation of added B in lime-amended acid soils.…”
Section: Introductionmentioning
confidence: 99%